Criminalization of the Transfer of Fiduciary Guarantee Objects Without Consent: A Study Result of the Case No. 118/Pid.Sus/2024/PN Pgp - Agustiyanto, Piko; Saliman, Abdul Rasyid; Tamrin, Husni (International Journal of Science and Society, 2025)
This research aims to examine the criminalisation aspect of the act of transferring the object of fiduciary guarantee without the written consent of the fiduciary recipient in the perspective of criminal law, with a case study of the Pangkalpinang District Court Decision Number 118/Pid.Sus/2024/PN Pgp. In this case, the defendant was sentenced to criminal punishment for transferring the vehicle which was the object of fiduciary guarantee to a third party without the consent of the financing party. The research method used in this research is normative juridical with a case approach. The results of the analysis show that the criminalisation of the act aims to provide legal protection for the financing institution, but on the other hand it raises a debate because the act of civil default is qualified as a criminal act. This study recommends the need for harmonisation between civil and criminal law in responding to violations of fiduciary agreements so as not to cause excessive criminalisation and still uphold the principle of justice.